The Analysis of Green Supply Chain Management, Green Capability, and Economic Performance: A Study of Catering SMEs in The Special Region of Yogyakarta, Indonesia - Liestyana, Yuli; Utami, Yekti; Satmoko, Agung; Amal, Firman Ihlasul (Journal of International Conference Proceedings, 2022)
The purpose of the paper is to analyze the effect of green supply chain management on economic performance in catering SMEs in the province of the Special Region of Yogyakarta, Indonesia. In the previous research, those relationships are mediated by green capability as the intervening variable. This study uses a purposive sampling technique. There are 50 catering SMEs as samples in this study. The questionnaire data were analyzed using the SEM (Structural Equation Modeling) analysis method using the SmartPLS v.3.2.7 software. The results of this study are different from the previous research. The differences may come from the highly distinct population from the prior research subjects. Therefore, some hypotheses are not accepted. Only one hypothesis is accepted, which is about the effect of green capability on economic performance. The limitation of this research is that it only conducts research in one sector, and the differences in circumstances and places of research cause research results to differ significantly from previous studies. In addition, the results of this study cannot be generalized and do not represent existing businesses in other sectors.